The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/biomedicines10071722
|View full text |Cite
|
Sign up to set email alerts
|

Assisted Reproductive Technique and Abnormal Cord Insertion: A Systematic Review and Meta-Analysis

Abstract: Abnormal cord insertion (ACI) is associated with adverse obstetric outcomes; however, the relationship between ACI and assisted reproductive technology (ART) has not been examined in a meta-analysis. This study examines the association between ACI and ART, and delivery outcomes of women with ACI. A systematic review was conducted, and 16 studies (1990–2021) met the inclusion criteria. In the unadjusted pooled analysis (n = 10), ART was correlated with a higher rate of velamentous cord insertion (VCI) (odds rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…The associated pathology for VP is mainly fetal heart abnormalities, and the risk factors are assisted reproduction, low-lying placenta, placenta previa, accessory lobe/bilobated placenta, and multiple pregnancy [ 6 ]. VP prenatally with VCI may be associated with several pregnancy outcomes, such as preterm delivery and postpartum hemorrhage [ 6 , 10 , 11 ]. The antenatal diagnosis increases the neonatal survival from 44% to 97% and improves the neonatal outcome [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The associated pathology for VP is mainly fetal heart abnormalities, and the risk factors are assisted reproduction, low-lying placenta, placenta previa, accessory lobe/bilobated placenta, and multiple pregnancy [ 6 ]. VP prenatally with VCI may be associated with several pregnancy outcomes, such as preterm delivery and postpartum hemorrhage [ 6 , 10 , 11 ]. The antenatal diagnosis increases the neonatal survival from 44% to 97% and improves the neonatal outcome [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present systematic review showed that type II vasa previa accounts for approximately 20% of all vasa previa cases. A recent study reported that the incidence of vasa previa may be increasing with the increasing number of ART pregnancies [ 54 ]; however, the trends of type II vasa previa are still unknown. If ART pregnancy is associated with an increased prevalence of abnormal placenta; the incidence of type II vasa previa is expected to increase.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike bilobed placenta and succenturiate lobe, the development of velamentous cord insertion has been well discussed, and two major hypotheses have been proposed (trophotropism hypothesis and polarity hypothesis) [ 54 , 62 ]. The trophotropism hypothesis was proposed to explain the development of velamentous cord insertion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous publications con rmed that vasa previa [24][25][26][27] and abnormal cord insertion [27][28][29] are more frequent in pregnancies conceived by assisted reproductive technology. Nonetheless, no study has further compared the odds of abnormal umbilical cord after PGT technology versus IVF/ICSI technology.…”
Section: Discussionmentioning
confidence: 99%